Study the Effect of Counseling on Early Initiation of Breastfeeding with Media Breastfeeding E-books - Rahmawati, Elsa Budi Sihsilya; Saputri, Poppy Farantia (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Early Initiation of Breastfeeding (EIBF) is the first step in the success of a baby to learn to suckle first early after birth. The coverage of EIBF is still very low in 2010 (29.3%) and in 2013 it became (34.5%). This study aims to analyze the influence of Successful Breastfeeding e-book on the Practice EIBF. The research design used a quasi experiment design with pre-post-test control group design. The study was conducted on 54 pregnant women 3rd trimester with purposive sampling method (March-June 2018). Data analysis used an independent t-test and Chi square test. The results showed that there was an effect of e-book on knowledge of pregnant women (p value 0.00). Counseling with Successful Breastfeeding e-books affects the Practice of EIBF (p value 0.017). A commitment is needed from health workers, especially those related to pregnant women and giving birth to provide counseling related to the importance of EIBF.